Norovirus-induced gastroenteritis presenting with reversible quadriparesis in an adult suggesting transient intramyelinic edema: A rare case report - Saran, Sai; Neyaz, Zafar; Azim, Afzal (Indian Journal of Case Reports, 2019)
Neuromuscular weakness with no plausible cause other than critical illness has been labeled as an intensive care-acquired weakness. There are myriad causes of neuromuscular weakness in intensive care unit (ICU). Here, we present the case of an adult with a diagnosis of acute gastroenteritis due to Norovirus with acute kidney injury and sepsis presenting with acute flaccid quadriparesis which recovered fully before ICU discharge. Magnetic resonance imaging brain of this patient suggested white matter diffusion restriction with normalization of diffusion abnormality after 2 months, suggesting “transient intramyelinic edema.” We highlight that Norovirus gastroenteritis can present as myelin sheath edema causing quadriparesis mimicking other etiologies for neuromuscular weakness in ICU and discussed the various differential diagnoses of white matter demyelination and diffusion restriction in this case report.